Positive electrode composite material, manufacturing method of positive electrode composite material and lithium ion battery
By controlling the particle size and recovery specific surface area of the carbon material, a positive electrode composite material with a recovery specific surface area of more than 1100m2/g was prepared, which solved the problem of reduced cycle characteristics of the sulfur and carbon material composite material during the thickening process and achieved high capacity and stable lithium-ion battery performance.
Patent Information
- Application Number
- CN202480015894.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-10
- Filing Date
- 2024-02-29
- Publication Date
- 2025-10-17
Smart Images

Figure CN120814064A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a positive electrode composite material, a method for producing a positive electrode composite material, and a lithium ion battery. BACKGROUND
[0002] As a high-capacity positive electrode composite material used in an all-solid lithium ion battery, a composite material of a sulfur-based active material and a carbon material has been proposed (Patent Documents 1 to 3, Non-Patent Documents 1 and 2).
[0003] In further energy density of lithium ion batteries, for example, the content of active material that increases the stored energy in the battery is considered. Specifically, it is considered to make the electrode as a layer containing an active material thicker.
[0004] PRIOR ART DOCUMENTS
[0005] PATENT DOCUMENTS
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-72781
[0007] Patent Document 2: Japanese Patent Application Publication No. 2014-529853
[0008] Patent Document 3: Japanese Patent Application Publication No. 2014-11033
[0009] Patent Document 4: International Publication No. 2022 / 260056
[0010] NON-PATENT DOCUMENTS
[0011] Non-Patent Document 1: Small 2021, 2105678
[0012] Non-Patent Document 2: Adv. Mater. Interfaces 2022, 2200539 SUMMARY
[0013] In the case where a composite material of sulfur as an active material and a carbon material is used for a positive electrode, if the electrode is formed to be thick, there is a technical problem that the influence of expansion and contraction of sulfur becomes large, and the cycle characteristics decrease.
[0014] One of the objects of the present application is to provide a positive electrode composite material that enables thickening of a positive electrode and suppresses a decrease in cycle characteristics.
[0015] The present inventors have studied the relationship between the dispersion state of sulfur in a positive electrode composite material using a composite material of sulfur and a carbon material and a sulfide solid electrolyte and the particle diameter of the carbon material. As a result, it was presumed that when the particle diameter of the carbon material forming the composite material is large, the amount of sulfur remaining in the pores of the carbon material increases, and the expansion and contraction during charge and discharge become large. It was concluded that due to the expansion and contraction during charge and discharge, the conductive path in the positive electrode is broken, and the cycle characteristics decrease.
[0016] Furthermore, it was found that in a case where the specific surface area of a treatment product from which the sulfur and the sulfide solid electrolyte are removed from the composite material is large, a positive electrode composite material capable of suppressing a decrease in cycle characteristics can be obtained.
[0017] According to the present application, the following positive electrode composite material and the like are provided.
[0018] 1. A positive electrode composite material comprising a carbon-sulfur composite and a sulfide solid electrolyte,
[0019] The specific surface area of a treatment product from which the sulfur and the sulfide solid electrolyte are removed from the positive electrode composite material is 1100 m 2 / g or more.
[0020] 2. The positive electrode composite material according to 1, wherein the sulfide solid electrolyte comprises lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms.
[0021] 3. The positive electrode composite material according to 2, wherein the sulfide solid electrolyte comprises two or more kinds of halogen atoms.
[0022] 4. The positive electrode composite material according to 2, wherein the mass ratio (P / sulfide solid electrolyte) of the phosphorus atoms (P) in the sulfide solid electrolyte is less than 0.20.
[0023] 5. The positive electrode composite material according to any one of 1 to 4, wherein the total mass (S) of the sulfur and the sulfur of a discharge product of the sulfur is 20 mass% or more.
[0024] 6. A method for manufacturing a positive electrode composite material, comprising:
[0025] Process A, complexing a carbon material with sulfur to obtain a carbon-sulfur composite;
[0026] Process B, mixing and pulverizing the carbon-sulfur composite with a sulfide solid electrolyte to obtain a positive electrode composite material,
[0027] In the process B, the treatment product from which the sulfur and the sulfide solid electrolyte are removed from the positive electrode composite material is prepared so that the specific surface area becomes 1100 m 2 / g or more.
[0028] 7. The production method according to 6, wherein the average particle diameter of the carbon material is 50 μm or less.
[0029] 8. The production method according to 6 or 7, wherein the specific surface area of the carbon material is 2300 m 2 / g or more.
[0030] 9. The production method according to any one of 6 to 8, wherein the mixing pulverization of the process B is performed using a planetary ball mill.
[0031] 10. A positive electrode composite obtained by the production method according to any one of 6 to 9.
[0032] 11. A positive electrode composed of the positive electrode composite according to any one of 1 to 5 and 10.
[0033] 12. The positive electrode according to 11, having a thickness of 35 μm or more.
[0034] 13. A positive electrode, wherein the recovered specific surface area of a processed product in which sulfur and a sulfide solid electrolyte are removed is 1100 m 2 / g or more.
[0035] 14. A lithium ion battery comprising the positive electrode according to any one of 11 to 13.
[0036] According to the present application, it is possible to provide a positive electrode composite which enables thickening of a positive electrode and suppresses a decrease in cycle characteristics. BRIEF DESCRIPTION OF DRAWINGS
[0037] Figure 1 is a graph showing the results of constant current charge-discharge tests of the all-solid lithium ion batteries produced in Examples 1, 2 and Comparative Examples 1, 2. DETAILED DESCRIPTION
[0038] 1. Positive electrode composite
[0039] The positive electrode composite of one embodiment of the present application contains a carbon-sulfur composite and a sulfide solid electrolyte. Furthermore, it is characterized in that the recovered specific surface area of a processed product in which sulfur and the sulfide solid electrolyte are removed from the positive electrode composite is 1100 m 2 / g or more. The recovered specific surface area of 1100 m 2 / g or more indicates that the particle diameter of the carbon material contained in the positive electrode composite is sufficiently small and the amount of elemental sulfur and discharge products of elemental sulfur held by the carbon material is appropriate.
[0040] If the particle diameter of the carbon material is large, the amount of sulfur held in the fine pores of the carbon material increases. If the amount of sulfur held by one carbon material particle is large, the expansion and contraction during charge and discharge become large, and thus the conductive path in the positive electrode is broken and the cycle characteristics decrease.
[0041] By using the positive electrode composite material of the present embodiment, expansion and contraction at the time of charge and discharge can be suppressed, and thus thickening of the positive electrode can be achieved, and a battery with less reduction in cycle characteristics can be obtained.
[0042] The recovered specific surface area refers to the specific surface area of the treated product (mainly carbon material) from which the solid electrolyte and sulfur are removed from the positive electrode composite material, by the following procedures. The specific treatment is described in the examples.
[0043] (1) Solid electrolyte removal procedure
[0044] The solid electrolyte is removed from the positive electrode composite material by dispersing the positive electrode composite material in excess solvent. As the solvent, ethanol and the like can be exemplified.
[0045] (2) Sulfur removal procedure
[0046] The precipitate recovered in the above procedure (1) is subjected to heating and drying, and the solvent and sulfur are removed from the precipitate.
[0047] The specific surface area of the treated product obtained through the above (1) and (2) is taken as the recovered specific surface area.
[0048] If the particle diameter of the carbon material is large, sulfur that has penetrated into the deep portion of the carbon material is not removed and remains in the carbon material, and thus the recovered specific surface area becomes small. On the other hand, if the particle diameter of the carbon material is small, most of the sulfur held by the carbon material is removed, and thus the recovered specific surface area becomes large.
[0049] In one embodiment, the recovered specific surface area is preferably 1200 m 2 / g or more, and more preferably 1300 m 2 / g or more. The upper limit is not particularly limited, and is 2000 m 2 / g or less.
[0050] In addition, the recovered specific surface area of the treated product is not greater than the specific surface area of the carbon material as the starting material.
[0051] In the present application, the specific surface area can be measured by the Brenauer-Emmet-Telle (BET) method, the BJH method (Barrett-Joyner-Halenda method).
[0052] Specifically, it can be calculated using the nitrogen adsorption isotherm obtained by causing a sample to adsorb nitrogen at liquid nitrogen temperature.
[0053] As the measuring device, for example, the specific surface area and pore distribution measuring device (Autosorb-3) manufactured by the company of Conta can be used to perform the measurement.
[0054] The positive electrode composite of the present embodiment can be produced, for example, by the production method of the present application described below.
[0055] 2. Production method of positive electrode composite
[0056] The production method of the positive electrode composite of an embodiment of the present application includes the following processes (A) and (B).
[0057] Process (A): process of complexing a carbon material with sulfur to obtain a carbon-sulfur composite
[0058] Process (B): process of mixing and pulverizing the carbon-sulfur composite with a sulfide solid electrolyte to obtain a positive electrode composite
[0059] [Process (A)]
[0060] In process (A), a carbon material is complexed with sulfur to obtain a carbon-sulfur composite.
[0061] As the carbon material, a material having electronic conductivity, a specific surface area of 2300 m 2 / g or more, and capable of being complexed with sulfur can be used. A porous carbon material having a plurality of fine pores is preferred.
[0062] As examples of the porous carbon material, carbon black, mesoporous carbon, carbon nanotube, acetylene black, furnace black, carbon nanohorn, fullerene, graphene, graphite, amorphous carbon, carbon fiber, natural graphite, artificial graphite, and activated carbon, etc. can be given. These can be used alone or two or more kinds thereof can be used in combination.
[0063] The specific surface area is preferably 2500 m 2 / g or more, and particularly preferably 2700 m 2 / g or more. The upper limit of the specific surface area is not particularly limited, and is preferably less than 6000 m 2 / g. If it is 6000 m 2 / g or more, the bulk density becomes extremely small, and the handling can become difficult.
[0064] As the elemental sulfur (sulfur), there is no particular limitation, and the purity is preferably 95 mass% or more, more preferably 96 mass% or more, and particularly preferably 97 mass% or more.
[0065] As the crystal system of the elemental sulfur, α-sulfur (orthorhombic system), β-sulfur (monoclinic system), γ-sulfur (monoclinic system), amorphous sulfur, etc. can be given. These can be used alone or two or more kinds thereof can be used in combination. The elemental sulfur becomes a molten liquid by heating.
[0066] The carbon material is compounded with sulfur to form a carbon-sulfur composite. For example, the carbon material and elemental sulfur are mixed and sealed, and the mixture is heated to melt the elemental sulfur and allow the elemental sulfur to infiltrate into the pores, thereby producing the carbon-sulfur composite.
[0067] The amount of the elemental sulfur mixed with respect to the total of the carbon material and the elemental sulfur is preferably 30% by mass or more. To increase the capacity of the battery, the more elemental sulfur mixed, the better, but if too much, the electronic conductivity of the positive electrode decreases. The amount of the elemental sulfur mixed is more preferably 50% by mass or more, and further preferably 70% by mass or more. In addition, the amount of the elemental sulfur mixed is preferably 90% by mass or less.
[0068] In one embodiment, the mixture of the carbon material and the elemental sulfur is heated at a temperature of the melting point of the elemental sulfur (about 115°C) or higher in a sealed state. The heating temperature is adjusted depending on the carbon material and the elemental sulfur, but is preferably 130°C or higher, and more preferably 150°C or higher. The upper limit of the heating temperature is a temperature of the boiling point of the elemental sulfur (about 445°C) or lower. The heating time is preferably 0.1 to 24 hours.
[0069] The carbon-sulfur composite is obtained by cooling after heating. A pulverization process can be performed as needed after cooling.
[0070] The carbon-sulfur composite retains the elemental sulfur and the discharge product of the elemental sulfur on the surface and / or in the pores of the carbon material. The carbon material retains the particle size thereof small, and thus, in addition to the function of smoothly supplying electrons and ions, the conduction of electrons to the entire positive electrode becomes easy due to the high electronic conductivity of the carbon material.
[0071] In the positive electrode composite material, a part or all of the elemental sulfur infiltrates into the pores of the carbon material. The elemental sulfur that does not infiltrate into the pores exists in a manner of coating a part or the entire of the carbon material. By analyzing the particle cross section of the carbon material using an analysis method capable of performing element mapping such as SEM-EDS and TEM-EDX, the overlap of the elements derived from the carbon material and the sulfur element is evaluated, and it is possible to confirm whether or not the sulfur infiltrates into the pores of the carbon material.
[0072] In one embodiment, the content of the elemental sulfur in the positive electrode composite material is large, and thus, the elemental sulfur exists also outside the pores of the carbon material. In this case, the substance obtained by compounding the elemental sulfur with the carbon material becomes a block like a particle, but can be powdered by mechanical pulverization.
[0073] [Process (B)]
[0074] In process (B), the carbon-sulfur composite and the sulfide solid electrolyte are mixed and pulverized to produce the positive electrode composite material. In process B, the specific surface area of the processed product from which the carbon-sulfur composite and the sulfide solid electrolyte are removed from the positive electrode composite material is 1100 m2 / g or more.2 / g or more.
[0075] In the process (B), the carbon-sulfur composite and the sulfide solid electrolyte are mixed and pulverized by applying mechanical stress thereto. Here, the "application of mechanical stress" means mechanical application of a shearing force, an impact force, or the like. As a method of applying mechanical stress, for example, a pulverizer such as a planetary ball mill, a vibration mill, a roll mill, or the like, a kneader, or the like can be exemplified.
[0076] By this process, a part of the carbon-sulfur composite and the sulfide solid electrolyte can be pulverized.
[0077] As the content of the sulfide solid electrolyte, when the carbon-sulfur composite is taken as 100 parts by mass, it is preferably 5 to 200 parts by mass, and more preferably 10 to 120 parts by mass. When the content of the solid electrolyte is 5 parts by mass or less, ion conduction is not sufficiently obtained, and when it is 200 parts by mass or more, the content rate of the active material decreases, and it is difficult to increase the energy density.
[0078] In one embodiment, the content rate of elemental sulfur with respect to the total of the carbon-sulfur composite and the sulfide solid electrolyte is 20% by mass or more. The content rate of elemental sulfur is preferably 30% by mass or more, and more preferably 40% by mass or more. When the content rate of elemental sulfur is high, the capacity of the battery becomes large, but the electron conductivity in the positive electrode decreases. The upper limit of the content rate of elemental sulfur is 80% by mass or less.
[0079] In order to make the recovered specific surface area 1100 m 2 / g or more, the specific surface area, the average particle diameter, and the processing conditions of the pulverizer (for example, the type of the pulverizing medium, the processing time, and the rotation speed) of the carbon material can be adjusted.
[0080] The average particle diameter (D 50 ) of the carbon material as a raw material is preferably 50 μm or less. The average particle diameter of the carbon material can be 40 μm or less, and can also be 10 μm or less. The lower limit of the average particle diameter is not particularly limited, and is usually 0.1 μm.
[0081] In the present specification, the average particle diameter (D 50 ) is the particle diameter at which 50% of the entire volume is reached when the cumulative curve of the particle diameter distribution is plotted, starting from the particle having the smallest particle diameter. The volume distribution can be measured, for example, using a laser diffraction / scattering type particle diameter distribution measuring device.
[0082] The smaller the average particle diameter of the carbon material and the larger the specific surface area, the more difficult it is to leave coarse carbon-sulfur composite particles, and the recovered specific surface area easily becomes 1100 m 2 / g or more.
[0083] For example, in the case of using a planetary ball mill in the mixed pulverization, the kind of the pulverization medium, the processing time, the rotation speed are controlled in consideration of the average particle diameter or the like of the carbon material as the raw material. In the case of using a carbon material having a large average particle diameter as the raw material, by performing the pulverization treatment as long as possible and with a strong energy under conditions that do not cause deterioration of the material, the particle diameter of the carbon-sulfur composite in the finally obtained positive electrode composite can be uniformly reduced. Thereby, the removal of the solid electrolyte and the removal of sulfur can be performed up to the inside of the composite particles, and the specific surface area can be recovered to be large.
[0084] Further, it is effective to use a carbon material having a small average particle diameter, or a carbon material in a fibrous shape having a high aspect ratio and being easy to break, or the like, a carbon material having no coarse particles even if not pulverized, or a carbon material having a shape that can be finely pulverized in a short time.
[0085] More specifically, in the case of using a planetary ball mill (FRITSCH Co., Ltd.: Model P-7) used in the present embodiment, the rotation speed of the planetary ball mill is preferably 100 rpm or more and 600 rpm or less, and more preferably 150 rpm or more and 400 rpm or less.
[0086] For example, in the case of using a zirconia ball as the pulverization medium, the diameter thereof is preferably 0.2 to 20 mm.
[0087] In one embodiment, for the positive electrode composite, heating is performed after the step of mixing the above-described carbon-sulfur composite and the sulfide solid electrolyte. By recrystallizing the solid electrolyte whose crystallinity is reduced in the mixing step or the effect of interface formation by heating, the ion conductivity can be improved, and thus the battery characteristics can be improved.
[0088] The sulfide solid electrolyte used in the present embodiment is a solid electrolyte containing at least a sulfur atom and exhibiting ion conductivity caused by a metal atom contained therein; and is a solid electrolyte containing, in addition to the sulfur atom, preferably a lithium atom and a phosphorus atom, and more preferably a lithium atom, a phosphorus atom, and a halogen atom, and having ion conductivity caused by the lithium atom.
[0089] As the sulfide solid electrolyte, it can be an amorphous sulfide solid electrolyte, or a crystalline sulfide solid electrolyte.
[0090] (Amorphous Sulfide Solid Electrolyte)
[0091] As the amorphous sulfide solid electrolyte, any one can be used without particular limitation as long as it contains at least a sulfur atom and exhibits ion conductivity caused by metal atoms contained therein. As representative amorphous sulfide solid electrolytes, for example, a solid electrolyte containing a sulfur atom, a lithium atom, and a phosphorus atom composed of lithium sulfide and phosphorus sulfide such as Li2S-P2S5 can be preferably exemplified; a solid electrolyte composed of lithium sulfide, phosphorus sulfide, and lithium halide such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr; and a solid electrolyte further containing an oxygen element, a silicon element, or the like such as Li2S-P2S5-Li2O-LiI, Li2S-SiS2-P2S5-LiI. From the viewpoint of obtaining higher ion conductivity, a solid electrolyte composed of lithium sulfide, phosphorus sulfide, and lithium halide such as Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-LiI-LiBr is preferable.
[0092] The kind of elements constituting the amorphous sulfide solid electrolyte can be confirmed by, for example, an ICP emission spectrometric analysis device.
[0093] In the case where the amorphous sulfide solid electrolyte has at least Li2S-P2S5, from the viewpoint of high chemical stability and obtaining higher ion conductivity, the molar ratio of Li2S to P2S5 is preferably 30 to 85: 15 to 70, more preferably 40 to 80: 20 to 60, and further preferably 45 to 78: 22 to 55.
[0094] For example, in the case where the amorphous sulfide solid electrolyte is Li2S-P2S5-LiI-LiBr, the total content of lithium sulfide and diphosphorus pentasulfide is preferably 30 to 95 mol%, more preferably 35 to 90 mol%, and further preferably 40 to 85 mol%. In addition, the proportion of lithium bromide with respect to the total of lithium bromide and lithium iodide is preferably 1 to 99 mol%, more preferably 20 to 90 mol%, further preferably 40 to 80 mol%, and particularly preferably 50 to 70 mol%.
[0095] In the case where the amorphous sulfide solid electrolyte contains a lithium atom, a sulfur atom, a phosphorus atom, and a halogen atom, the mixing ratio (molar ratio) of these atoms is preferably 1.0 to 1.8: 1.0 to 2.0: 0.1 to 0.8: 0.01 to 0.6, more preferably 1.1 to 1.7: 1.2 to 1.8: 0.2 to 0.6: 0.05 to 0.5, and further preferably 1.2 to 1.6: 1.3 to 1.7: 0.25 to 0.5: 0.08 to 0.4.
[0096] Further, in the case where bromine and iodine are used as the halogen atom, the mixing ratio (molar ratio) of lithium atom, sulfur atom, phosphorus atom, bromine atom, and iodine atom is preferably 1.0-1.8: 1.0-2.0: 0.1-0.8: 0.01-0.3: 0.01-0.3, more preferably 1.1-1.7: 1.2-1.8: 0.2-0.6: 0.02-0.25: 0.02-0.25, more preferably 1.2-1.6: 1.3-1.7: 0.25-0.5: 0.03-0.2: 0.03-0.2, further preferably 1.35-1.45: 1.4-1.7: 0.3-0.45: 0.04-0.18: 0.04-0.18. By setting the mixing ratio (molar ratio) of lithium atom, sulfur atom, phosphorus atom, and halogen atom within the above range, a solid electrolyte having a higher ion conductivity of the sulfidic crystalline lithium super ionic conductor region II-type crystal structure described later can be easily obtained.
[0097] Further, the shape of the amorphous sulfidic solid electrolyte is not particularly limited, and for example, a particle shape can be exemplified. The average particle diameter (D50) of the amorphous sulfidic solid electrolyte in the particle shape is, for example, in the range of 0.01 μm to 500 μm, 0.1 to 200 μm. 50 For example, the average particle diameter (D50) of the amorphous sulfidic solid electrolyte in the particle shape is, for example, in the range of 0.01 μm to 500 μm, 0.1 to 200 μm.
[0098] (Crystalline sulfidic solid electrolyte)
[0099] As the crystalline sulfidic solid electrolyte, for example, a so-called glass ceramic obtained by heating the above-described amorphous sulfidic solid electrolyte to a crystallization temperature or more can be used, and a sulfidic solid electrolyte having the following crystal structure can be used.
[0100] As the crystal structure that the crystalline sulfidic solid electrolyte containing lithium atom, sulfur atom, and phosphorus atom can have, a Li3PS4 crystal structure, a Li4P2S6 crystal structure, a Li7PS6 crystal structure, a Li7P3S 11 a crystal structure having peaks near 2θ = 20.2° and 23.6° (for example, Japanese Patent Application Publication No. 2013-16423), and the like.
[0101] Further, as the crystal structure that the crystalline sulfidic solid electrolyte containing lithium atom, sulfur atom, phosphorus atom, and halogen atom can have, a Li 4-x Ge 1-x P xS4-type thio-LISICON Region II-type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148(7) A742-746 (2001)), and Li 4-x Ge 1-x P x S4-type thio-LISICON Region II-type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148(7) A742-746 (2001)), and Li 4- x Ge 1-x P x S4-type thio-LISICON Region II-type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148(7) A742-746 (2001)), and Li 4- x Ge 1-x P x S4-type thio-LISICON Region II-type crystal structure (see Kanno et al., Journal of The Electrochemical Society, 148(7) A742-746 (2001)), and Li
[0102] In X-ray diffraction measurement using Cu Kα rays, diffraction peaks of the Li3PS4crystal structure are present, for example, near 2θ = 17.5°, 18.3°, 26.1°, 27.3°, 30.0°, diffraction peaks of the Li4P2S6crystal structure are present, for example, near 2θ = 16.9°, 27.1°, 32.5°, diffraction peaks of the Li7PS6crystal structure are present, for example, near 2θ = 15.3°, 25.2°, 29.6°, 31.0°, diffraction peaks of the Li7P3S 11 diffraction peaks of the Li7P3S 4-x Ge 1-x P x diffraction peaks of the Li7P3S 4-x Ge 1-x P xThe diffraction peaks of the S4-type thio-LISICON Region II-type similar crystal structure, for example, appear near 2θ = 20.2°, 23.6°. In addition, these peak positions can fluctuate within a range of ±0.5°.
[0103] Further, as the crystal structure of the crystalline sulfide solid electrolyte, a argyrodite-type crystal structure can also be exemplified. As the argyrodite-type crystal structure, for example, Li7PS6 crystal structure; a crystal represented by the composition formula Li 7-x P 1-y Si y S6 and Li 7+x P 1-y Si y S6 (x is -0.6 to 0.6, and y is 0.1 to 0.6) ; a crystal represented by Li 7-x-2y PS 6-x-y Cl x (0.8≤x≤1.7, 0<y≤-0.25x+0.5) ; a crystal represented by Li 7-x PS 6-x Ha x (Ha is Cl or Br, and x is preferably 0.2 to 1.8).
[0104] Among the above crystal structures, as the crystal structure possessed by the crystalline sulfide solid electrolyte, a Li3PS4 crystal structure, a thio-LISICON Region II-type crystal structure, and an argyrodite-type crystal structure are preferable.
[0105] As the shape of the crystalline sulfide solid electrolyte, there is no particular limitation, and for example, a particle shape can be exemplified. The average particle diameter (D 50 ) of the crystalline sulfide solid electrolyte in the particle shape is, similarly to the average particle diameter (D 50 ) of the above amorphous sulfide solid electrolyte, for example, in the range of 0.01 μm to 500 μm, 0.1 to 200 μm.
[0106] In one embodiment, the sulfide solid electrolyte can contain a halogen atom, and the sulfide solid electrolyte preferably contains two or more kinds of halogen atoms. Further, it is preferable to have a sulfurized crystalline lithium superionic conductor region II type crystal structure. Further, the mass ratio of phosphorus atoms in the sulfide solid electrolyte (P / sulfide solid electrolyte) is preferably less than 0.20. It is particularly preferable to be less than 0.15, and further preferable to be less than 0.13. Thereby, even if mixed and pulverized with a carbon-sulfur composite, the decrease in ion conductivity becomes small. Further, by making the ratio of phosphorus small, the sulfide solid electrolyte itself reacts at the time of discharge, and thus the influence of deterioration and swelling becomes small. Thereby, by maintaining the conduction path of electrons and lithium within the positive electrode composite material, high cycle characteristics can be expected.
[0107] In one embodiment, the above-described positive electrode composite material of the present application and the positive electrode composite material obtained by the production method of the present application can contain other components than the carbon material, sulfur, the discharge product of sulfur, and the sulfide solid electrolyte, and can also not contain them. The other components are not particularly limited, and for example, a binder, a solvent, a dispersant, and the like can be exemplified.
[0108] Here, a part or all of elemental sulfur changes to a discharge product at the time of battery reaction. Therefore, in the positive electrode composite material (positive electrode) of one embodiment, a discharge product of elemental sulfur is present. In the case where a discharge product is present, the sulfur contained in the positive electrode composite material is set to the total amount of sulfur contained in elemental sulfur and the discharge product.
[0109] As the discharge product of elemental sulfur, Li2S in a completely discharged state and Li2S2, Li2S4, Li2S6, Li2S8, and the like, which are lithium polysulfides as an intermediate stage, can be exemplified.
[0110] In one embodiment, the total mass (S) of sulfur in elemental sulfur and the discharge product of elemental sulfur is 20% by mass or more. The total mass (S) is preferably 30% by mass or more, and more preferably 40% by mass or more. If the total mass (S) is large, the capacity of the battery becomes large, but the electron conductivity in the positive electrode decreases. The upper limit of the total mass (S) is 80% by mass or less.
[0111] 3. Positive electrode and lithium ion battery
[0112] The positive electrode of one embodiment of the present application contains the above-described positive electrode composite material of the present application.
[0113] Further, in the positive electrode of another embodiment of the present application, the specific surface area of the treated product from which sulfur and the sulfide solid electrolyte are removed from the positive electrode is 1100 m 2 / g or more. The positive electrode of this embodiment can achieve thickening, and a battery with small decrease in cycle characteristics can be obtained. The specific surface area is the same as that of the above-described positive electrode composite material of the present application.
[0114] The thickness of the positive electrode can be 35 μm or more, and can also be 40 μm or more. In addition, it is usually 500 μm or less.
[0115] The lithium ion battery of an embodiment of the present application includes the positive electrode composite material or the positive electrode of the present application described above. For example, by using a solid electrolyte instead of a liquid electrolyte, an all-solid lithium ion battery can be manufactured. By using the positive electrode composite material of the present application, an all-solid lithium ion battery having good rate characteristics can be produced.
[0116] The all-solid lithium ion battery is mainly composed of a positive electrode layer, a negative electrode layer, and an electrolyte layer, but the positive electrode composite material of the present application is suitable as a constituent material of the positive electrode layer. The negative electrode layer and the electrolyte layer can be manufactured by a known method. In addition, a current collector is preferably used in addition to the positive electrode layer, the negative electrode layer, and the electrolyte layer, and a known current collector can be used as the current collector.
[0117] The solid electrolyte is not particularly limited, and for example, the sulfide solid electrolyte described above can be exemplified.
[0118] Example
[0119] Hereinafter, the present application will be specifically described based on examples. The present application is not limited by the examples.
[0120] (Example 1)
[0121] (1) Production of carbon-sulfur composite
[0122] Active carbon (MSF-A30M, Kansai Tetsu Chemical Corp., average particle diameter (D 50 ) 36 μm, specific surface area 3100 m 2 / g, fibrous shape) and sulfur were added to a glass bottle in a mass ratio of 3:7, and were sealed in a SUS tube container. By an electric furnace, heating was performed at 150°C for 6 hours and at 300°C for 2.75 hours, to obtain a powder of the active carbon-elemental sulfur composite.
[0123] (2) Production of sulfide solid electrolyte
[0124] 0.4127 g of lithium sulfide, 0.6655 g of phosphorus pentasulfide, 0.2137 g of lithium iodide, 0.2080 g of lithium bromide, and 10 zirconia-made balls each having a diameter of 10 mm were put into a 45 mL zirconia-made can, and were sealed. Using a planetary ball mill (Fritsch Co., Ltd., Model P-7), mixing (mechanical grinding) was performed at a rotation speed of 370 rpm for 40 hours, to obtain a powder. The obtained powder was heated at 195°C for 3 hours, to obtain a sulfide solid electrolyte. The content of P in the sulfide solid electrolyte was 0.12.
[0125] (3) Preparation of positive electrode composite materials
[0126] 0.7 g of the activated carbon-elemental sulfur composite powder obtained in (1) above and 0.3 g of the sulfide solid electrolyte obtained in (2) above were placed in a 45 mL zirconia can along with 10 zirconia balls having a diameter of 10 mm and sealed. A planetary ball mill (Fritsch, Model P-7) was used to grind the mixture at 370 rpm at room temperature for 20 hours to obtain a powder of the positive electrode composite material.
[0127] (4) Fabrication of all-solid-state lithium-ion batteries
[0128] 100 mg of the sulfide solid electrolyte prepared in (2) above was placed in a 10 mm diameter MACOR (registered trademark) cylinder and press-formed. The positive electrode composite material powder prepared in (3) above was placed on the pressurized surface so that the elemental sulfur content was 3.5 mg, and press-formed again. An all-solid-state battery was produced by placing indium foil and lithium foil on the pressurized surface opposite to the positive electrode composite material and pressurizing.
[0129] (Example 2)
[0130] The activated carbon (MSF-A30M) in Example 1 was changed to MSC30-SSS (produced by Kansai Thermochemical, with an average particle size (D 50 )3.2μm, specific surface area3016m 2 / g), a positive electrode composite material powder was obtained in the same manner as in Example 1 except for the above.
[0131] A full solid-state battery was produced in the same manner as in Example 1 except that the obtained positive electrode composite material powder was used.
[0132] (Comparative Example 1)
[0133] The activated carbon (MSF-A30M) in Example 1 was changed to MSC30 (produced by Kansai Thermochemical, with an average particle size (D 50 )56μm, specific surface area 3200m 2 / g), a positive electrode composite material powder was obtained in the same manner as in Example 1 except for the above.
[0134] A full solid-state battery was produced in the same manner as in Example 1 except that the obtained positive electrode composite material powder was used.
[0135] (Comparative Example 2)
[0136] MSC30-SS (produced by Kansai Thermochemical, average particle size (D 50)5.3 μm, specific surface area 3087 m 2 (g) 0.2 g of the mixed powder was put together with 40 g of zirconia balls having a diameter of 5 mm in a 45 mL zirconia pot, and the pot was closed. Using a planetary ball mill (Fritsch Co., model P-7), a pulverization treatment was performed at a rotation speed of 370 rpm for 4 hours under room temperature conditions, thereby obtaining a powder of the positive electrode composite material.
[0137] Since phosphorus pentasulfide was used as the solid electrolyte, the content of P in the solid electrolyte was 0.28.
[0138] [Assessment]
[0139] (Measurement of recovered specific surface area)
[0140] For the positive electrode composite materials produced in the examples and comparative examples, the specific surface area after the solid electrolyte removal step and the sulfur removal step was measured.
[0141] (1) Solid electrolyte removal step
[0142] 0.8 g of the positive electrode composite material was dispersed in an excess of 5 mL of ethanol, and ultrasonic waves were irradiated for 1 minute using an ultrasonic cleaner. The dispersion liquid was centrifuged at 12000 rpm for 1 minute using a table centrifuge (FB-4000), whereby the solid electrolyte was dissolved and removed. This operation was repeated 4 times until the supernatant was no longer colored.
[0143] (2) Sulfur removal step
[0144] The precipitate after the centrifugation was vacuum-dried at 200°C for 6 hours. Then, further heating at 600°C for 4 hours was performed in a glove box. Thereby, ethanol and sulfur were removed from the precipitate.
[0145] For each example and comparative example, the specific surface area of the treated product (recovered specific surface area) was measured.
[0146] (3) Measurement of recovered specific surface area of treated product
[0147] The measurement was performed using a specific surface area and pore distribution measuring device (Autosorb-3) manufactured by the company of Conta. The specific surface area was calculated by the Brenauer-Emmet-Telle (BET) multipoint method using the nitrogen adsorption isotherm obtained by adsorbing nitrogen gas to the precipitate obtained in the above operation at a liquid nitrogen temperature. The results are shown in Table 1.
[0148] [Table 1]
[0149] Restored specific surface area [m 2 / g]]]> Example 1 1353 Example 2 1588 Comparative Example 1 1003 Comparative Example 2 951
[0150] (Evaluation of Battery Characteristics)
[0151] The constant current charge and discharge test of the all-solid-state battery prepared in each example was performed. The cutoff potential of the constant current test was set to 0.8-2.2 V vs. Li-In, and the current density was set to the conditions shown in Table 2. The results are shown in Figure 1 .
[0152] [Table 2]
[0153]
[0154] Depend on Figure 1 It was confirmed that by setting the recovery specific surface area of the carbon material forming the composite material to 1100 m 2 / g or above, and the cycle characteristics of all-solid-state lithium-ion batteries are excellent.
[0155] Furthermore, it was confirmed that, as in Comparative Example 1, when the particle size of the carbon material forming the composite material was large and the recovery specific surface area was small, the cycle characteristics were deteriorated.
[0156] Furthermore, it can be seen that, as in Comparative Example 2, when the phosphorus content of the solid electrolyte is high, the capacity changes greatly during the initial charge and discharge, and the subsequent charge and discharge capacity remains constant but decreases. This is believed to be because the solid electrolyte deteriorates and expands and contracts during the initial charge and discharge, interrupting the electron and ion conduction pathways, thereby reducing the sulfur that contributes to charge and discharge.
[0157] Industrial Applicability
[0158] The cathode composite material of the present invention is suitable as a cathode of a lithium-ion battery. In addition, the lithium-ion battery of the present invention can be suitably used in batteries used in information-related equipment such as personal computers, cameras, and mobile phones, communication equipment, and vehicles such as electric cars.
[0159] While several embodiments and / or examples of the present invention have been described in detail above, it is readily apparent to those skilled in the art that many modifications may be made to these illustrative embodiments and / or examples without departing substantially from the novel teachings and effects of the present invention. Therefore, these numerous modifications are also encompassed within the scope of the present invention.
[0160] The contents of all documents described in this specification and the applications on which the present application claims priority under the Paris Convention are based are incorporated herein by reference.
Claims
1. A positive electrode composite material, characterized in that: Contains carbon-sulfur composite and sulfide solid electrolyte, The recovered specific surface area of the product obtained by removing the sulfur and the sulfide solid electrolyte from the positive electrode composite material is 1100 m 2 / g or above.
2. The positive electrode composite material according to claim 1, wherein The sulfide solid electrolyte includes lithium atoms, phosphorus atoms, sulfur atoms, and halogen atoms.
3. The positive electrode composite material according to claim 2, wherein The sulfide solid electrolyte contains two or more halogen atoms.
4. The positive electrode composite material according to claim 2, wherein The mass ratio of the phosphorus atoms P in the sulfide solid electrolyte, ie, P / sulfide solid electrolyte, is less than 0.
20.
5. The positive electrode composite material according to any one of claims 1 to 4, characterized in that The total mass S of sulfur in the sulfur and the discharge products of sulfur is 20 mass % or more.
6. A method for manufacturing a positive electrode composite material, characterized in that: include: Step A: Compounding a carbon material with sulfur to obtain a carbon-sulfur composite; Step B: mixing and grinding the carbon-sulfur composite and the sulfide solid electrolyte to obtain a positive electrode composite material. In the step B, the recovered specific surface area of the product obtained by removing the sulfur and the sulfide solid electrolyte from the positive electrode composite material is 1100 m 2 / g or more.
7. The method for producing a positive electrode composite material according to claim 6, wherein: The average particle size of the carbon material is 50 μm or less.
8. The method for producing a positive electrode composite material according to claim 6 or 7, wherein: The specific surface area of the carbon material is 2300 m 2 / g or above.
9. The method for producing a positive electrode composite material according to any one of claims 6 to 8, wherein: The mixing and pulverization in the step B was carried out using a planetary ball mill.
10. A positive electrode composite material, characterized in that: The method for producing a positive electrode composite material according to any one of claims 6 to 9 is obtained.
11. A positive electrode, characterized in that The positive electrode composite material is composed of the positive electrode composite material according to any one of claims 1 to 5 and claim 10.
12. The positive electrode according to claim 11, characterized in that The thickness is 35 μm or more.
13. A positive electrode, characterized in that The recovered specific surface area of the treated material after the removal of sulfur and sulfide solid electrolyte is 1100m 2 / g or above.
14. A lithium ion battery, characterized in that: A positive electrode according to any one of claims 11 to 13.
Citation Information
Patent Citations
Solid sulfide electrolyte material, solid-state lithium battery, and method for manufacturing solid sulfide electrolyte material
JP2013016423A
Positive electrode mixture
JP2014011033A
Electrode material for rechargeable batteries having activated carbon fibers
JP2014529853A
Positive electrode mixture, and all-solid type lithium sulfur battery
JP2015072781A
All-solid-state electrochemical element and sulfur-carbon complex
WO2022260056A1